Revolutionizing Fuel Efficiency with Optimal Octane Mixtures: Merevolusi Efisiensi Bahan Bakar dengan Campuran Oktan yang Optimal - Ibrahim, Mundir Ainun; Akbar , Ali (Universitas Muhammadiyah Sidoarjo, 2024)
Increasing the octane value of fuel can significantly improve engine performance and efficiency. This study explores mixing fuels with different octane ratings to achieve a desired balance of high octane and cost-effectiveness. Fuels with octane numbers 82, 86, 92, and 96 were mixed in various ratios (30%, 50%, 70%) of premium, pertalite, pertamax, and pertamax turbo. Results showed that mixtures like premium and pertalite (octane 85) and premium and pertamax turbo (octane 93) effectively increased octane levels. The study concludes that mixing fuels can enhance octane values and optimize fuel composition for better performance and cost efficiency. Future research could further explore various fuel types and ratios. Highlight: Mixing fuels increases octane rating and engine performance. Optimal fuel composition balances high octane and cost-effectiveness. Significant results with premium and pertamax turbo mixture. Keywoard: Octane Rating, Fuel Mixing, Engine Performance, Fuel Efficiency, Cost-Effective Fuel